The contractors of the spanish public administration in the administrative legislation of the 19th century - Gosálbez Pequeño, Humberto (Derecho Público Iberoamericano, 2017)
In Spain, the State requires capacity for contractors and prohibits contractor to certain citizens. In the nineteenth century, the administrative legislation for the construction and operation of public works is the most important regulation.